2020
DOI: 10.1111/exd.14208
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of α‐ and β‐adrenergic sweating during heat exposure and the influence of sex and training status

Abstract: While human eccrine sweat glands respond to adrenergic agonists, there remains a paucity of information on the factors modulating this response. Thus, we assessed the relative contribution of α-and β-adrenergic sweating during a heat exposure and as a function of individual factors of sex and training status. α-and β-adrenergic sweating was assessed in forty-eight healthy young men (n = 35) and women (n = 13) including endurance-trained (n = 12) and untrained men (n = 12) under non-heat exposure (temperate, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A likely reason for such conflicting evidence is the differing localised and systemic effects of oral βadrenoreceptor blockers that may indirectly modulate sweating during passive and exercise-induced sweating (Buono et al, 2010(Buono et al, , 2011. Local β-adrenergic blockade has been found to suppress local sweat rates during exercise-induced heat stress (Amano et al, 2017(Amano et al, , 2020. Recent in vivo evidence during exercise demonstrated that locally administered propranolol attenuated local sweat response, albeit only during higher-intensity submaximal exercise (80 -90% of maximum workload) in habitually active men, with no attenuation in untrained men (Amano et al, 2017).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…A likely reason for such conflicting evidence is the differing localised and systemic effects of oral βadrenoreceptor blockers that may indirectly modulate sweating during passive and exercise-induced sweating (Buono et al, 2010(Buono et al, , 2011. Local β-adrenergic blockade has been found to suppress local sweat rates during exercise-induced heat stress (Amano et al, 2017(Amano et al, , 2020. Recent in vivo evidence during exercise demonstrated that locally administered propranolol attenuated local sweat response, albeit only during higher-intensity submaximal exercise (80 -90% of maximum workload) in habitually active men, with no attenuation in untrained men (Amano et al, 2017).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Regular exercise training is associated with an increase in cardiorespiratory fitness, which is paralleled by an enhanced sweating response leading to improve performance during exercise, especially in the heat. It is believed that the exercise‐training‐induced activation of sweat glands may be responsible for the high sweat rate given the observation that pharmacological assessment of cholinergic sweating can be two times greater in endurance‐trained as compared to non‐endurance‐trained individuals (Amano et al., 2013, 2020b; Buono & Sjoholm, 1988; Inoue et al., 2014). Our findings confirm this hypothesis, but also advance new knowledge by demonstrating that the activity of TEA‐sensitive K + channels such as those associated with Ca 2+ ‐activated and possibly voltage‐gated K + channels, and therefore efflux of K + to extracellular space through these channels, does not modulate the underlying mechanisms mediating the augmented cholinergic sweat production in endurance‐trained men.…”
Section: Discussionmentioning
confidence: 99%
“…They were all members of the University Track and Field Club and were participating in regular competitions in both middle (e.g., 800–1500 m) and long (more than 1500 m) distance events. We limited the inclusion of endurance‐trained participants to those engaged in these events given prior reports demonstrating that middle‐ and long‐distance runners (Amano et al., 2020b; Tokizawa et al., 2016) but not sprinters (less than 400 m) (Amano et al., 2013) demonstrate an adaptive sweating response to regular exercise training. The non‐endurance participants were not engaged in any structured exercise activities for the previous 2 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local sweat rates on the forearm and chest were measured using the ventilated capsule method according to the methods used in our laboratory and described elsewhere [ 36 , 37 ]. A 3.14 cm 2 plastic capsule was affixed using topical glue (Collodion; Kanto chemical, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%